2016
DOI: 10.1002/aoc.3660
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) iodide supported on modified cellulose‐based nano‐magnetite composite as a biodegradable catalyst for the synthesis of 1,2,3‐triazoles

Abstract: Nano‐Fe3O4@Cellulose‐NH2‐CuI as a novel magnetically separable composite was prepared and fully characterized using various techniques including Fourier transform infrared, X‐ray photoelectron and energy‐dispersive X‐ray spectroscopies, X‐ray diffraction, field‐emission scanning and transmission electron microscopies, thermogravimetric analysis and vibrating sample magnetometry. To obtain an appropriate structure and also to describe to some extent the different kinds of metal–ligand interactions present in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 74 publications
(83 reference statements)
1
20
0
Order By: Relevance
“…It is worth mentioning that the results showed alkyl and aryl halides react better than haloketones in terms of yields and reaction times. The efficiency of CuI@[PMMA‐co‐MI] in click reaction was also compared with that of previously reported catalysts under various reaction conditions (Table ) . By comparison, it can be concluded that CuI@[PMMA‐co‐MI] as a novel nanocatalyst has several merits such as higher or comparable yield of the desired product in shorter reaction time.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is worth mentioning that the results showed alkyl and aryl halides react better than haloketones in terms of yields and reaction times. The efficiency of CuI@[PMMA‐co‐MI] in click reaction was also compared with that of previously reported catalysts under various reaction conditions (Table ) . By comparison, it can be concluded that CuI@[PMMA‐co‐MI] as a novel nanocatalyst has several merits such as higher or comparable yield of the desired product in shorter reaction time.…”
Section: Resultsmentioning
confidence: 95%
“…The efficiency of CuI@[PMMA-co-MI] in click reaction was also compared with that of previously reported catalysts under various reaction conditions (Table 7). [11,28,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] By comparison, it can be concluded that CuI@[PMMA-co-MI] as a novel nanocatalyst has several merits such as higher or comparable yield of the desired product in shorter reaction time. It should be mentioned that there are some reports in which higher yields of products were achieved using a low amount of catalyst loading.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Finally, the efficiency of CuI@HNTs‐2 N‐Sal for the above‐mentioned click reaction was compared with that of some previously reported catalysts under various reaction conditions (Table ) . Comparing the protocols, it can be concluded that use of CuI@HNTs‐2 N‐Sal led to higher or comparable yield of the desired product in shorter short reaction time.…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, these systems are usually homogeneous and suffer from inherent drawbacks: difficulty in separating the catalyst and product, environmental concern, and recyclability. Recent research in this area has focused on beneficial heterogeneous catalysis which can address these problems and has several advantages such as easier separation of catalyst and product(s), better recovery, allowing for reuse of the catalyst systems, and reduced metal contamination in the final products . In this context, magnetic nanoparticles (MNPs) are considered promising catalysts because of their response to an external magnetic field and are thus extensively used in a variety of important organic reactions .…”
Section: Introductionmentioning
confidence: 99%